Demands and possibilities for field-scale estimation of agricultural greenhouse gas balances - Palosuo, Taru; Heikkinen, Jaakko; Hilasvuori, Emmi; Kulmala, Liisa; Launiainen, Samuli; Lehtilä, Anniina; Leinonen, Ilkka; Liimatainen, Maarit; Salminen, Miia; Shurpali, Narasinha; Silfver, Tarja; Soinne, Helena; et al. (Elsevier, 2025)
Soil organic carbon (SOC) changes and greenhouse gas (GHG) emissions from agricultural soils contribute considerably to anthropogenic climate change. This draws attention to the management of agricultural fields and creates the need to assess and understand the resulting SOC changes and GHG balances and their drivers. Currently, GHG reporting systems such as national GHG inventories, carbon footprinting, and reporting practices in voluntary carbon markets largely apply rough estimation methods for these emissions. These methods do not relevantly cover the impacts of management or environmental factors on SOC changes or GHG emissions and their large spatial variability. At the same time, the rapid development of sensor techniques and data analysis methods creates opportunities for creating field-scale monitoring and reporting systems based on various data streams, including remote sensing. In this paper, we reviewed the existing GHG reporting systems, and how SOC changes and GHG emissions of agricultural soils are currently reported in them. We also reviewed the most important factors affecting field-scale GHG balances and SOC changes, and the current measurement techniques and modeling approaches applied, as well as novel integrated systems combining various data streams. Finally, we identified the key developments towards a credible, operational, and cost-efficient field-scale reporting system. We used Finland, which has already made considerable efforts to report and calculate agricultural emissions, as an example to highlight practical challenges.
Keywords: agricultural management; greenhouse gas balances; measurement and monitoring; reporting; soil carbon